Case study: Competition nutrition intakes during the open water swimming Grand Prix races in elite female swimmer - Kumstat, M.; Rybarova, S.; Thomas, A.; Novotny, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
The nutritional intake of elite open water swimmers during competition is not well established, and therefore this case study aims to provide new insights by describing the feeding strategies adopted by an elite female swimmer (28 yrs; height; 1.71 m; body mass: 60 kg; body fat: 16.0%) in the FINA open water Grand Prix 2014.Seven events of varying distances (15-88 km) and durations (3-12 hrs) were included. In all events, except one, feeds were provided from support boats. Swimmer and support staff were instructed to track in detail all foods and beverages consumed during the events. Nutritional information was gathered from the packaging and dietary supplements labels and analyzed by nutrition software. Mean carbohydrate (CHO) and protein intake reached 83 ± 5 g·h-1 and 12 ± 8 g·h-1, respectively. Fat intake was neglected (~1 g·h-1). Mean in-race energy intake reached 394 ± 26 kcal·h-1. Dietary supplements in the form of sport beverages and gels, containing multitransportable CHO, provided 40 ± 4 and 49 ± 6% of all CHO energy, respectively. Caffeine (3.6 ± 1.8 mg·kg-1 per event) and sodium (423 ± 16 mg·h-1) were additionally supplemented in all events. It was established that continuous intake of high doses of CHO and sodium and moderate dose of caffeine were an essential part of the feeding strategy for elite-level high intensity ultra-endurance open-water swimming races. A well scheduled and well-prepared nutrition strategy is believed to have ensured optimal individual performance during Grand Prix events.